The Role of Muscle Perfusion in the Age-Associated Decline of Mitochondrial Function in Healthy Individuals - Adelnia, Fatemeh; Cameron, Donnie; Bergeron, Christopher M.; Fishbein, Kenneth W.; Spencer, Richard G.; Reiter, David A.; Ferrucci, Luigi (Frontiers in Physiology, 2019)
Maximum oxidative capacity of skeletal muscle measured by in vivo phosphorus magnetic resonance spectroscopy (31P-MRS) declines with age, and negatively affects the whole-body aerobic capacity. However, it remains unclear whether the loss of oxidative capacity is caused by reduced volume and function of mitochondria or limited substrate availability secondary to impaired muscle perfusion. Therefore, we sought to elucidate the role of muscle perfusion on the age-related decline of muscle oxidative capacity and ultimately the whole-body aerobic capacity. Muscle oxidative capacity was assessed by 31P-MRS post-exercise phosphocreatine recovery time (τPCr), with higher τPCr reflecting lower oxidative capacity, in 75 healthy participants (48 men, 22-89 years) of the Genetic and Epigenetic Signatures of Translational Aging Laboratory Testing study. Muscle perfusion was characterized as an index of blood volume at rest using a customized diffusion-weighted MRI technique and analysis method developed in our laboratory. Aerobic capacity (peak-VO2) was also measured during a graded treadmill exercise test in the same visit. We found muscle oxidative capacity, peak-VO2, and resting muscle perfusion were significantly lower at older ages independent of sex, race, and body mass index (BMI). τPCr was significantly associated with resting muscle perfusion independent of age, sex, race and BMI (p-value = 0.004, β = -0.34). τPCr was also a significant independent predictor of peak-VO2 and in a mediation analysis significantly attenuate the association between muscle perfusion and peak-VO2 (34% reduction for β in perfusion). These findings suggest that the age-associated decline in muscle oxidative capacity is partly due to the impaired muscle perfusion and not mitochondrial dysfunction alone. Furthermore, our findings show that part of the decline in the whole-body aerobic capacity observed with aging is also due to reduced microvascular blood volume at rest, representing a basal capacity of the microvascular system, which is mediated by muscle oxidative capacity. This finding suggests potential benefit in interventions that target an overall increase in muscle perfusion for the restoration of energetic capacity and mitochondrial function with aging.